2021
DOI: 10.1186/s13287-021-02431-5
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-transported circRNA_0001236 enhances chondrogenesis and suppress cartilage degradation via the miR-3677-3p/Sox9 axis

Abstract: Objectives Aberrations in exosomal circular RNA (circRNA) expression have been identified in various human diseases. In this study, we investigated whether exosomal circRNAs could act as competing endogenous RNAs (ceRNAs) to regulate the pathological process of osteoarthritis (OA). This study aimed to elucidate the specific MSC-derived exosomal circRNAs responsible for MSC-mediated chondrogenic differentiation using human bone marrow-derived MSCs (hMSCs) and a destabilization of the medial meni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(39 citation statements)
references
References 39 publications
1
38
0
Order By: Relevance
“…Overexpression of Runx2 partially reversed the effect of the SMSC-155-5p-Exos [ 136 ] MSCs-Exos In vitro, co-culture with mouse chondrocytes NR circRNA_HIPK3/miR-124-3p/MYH9 MSCs-Exos overexpressing circHIPK3 improved IL-1β-induced chondrocyte injury. Mechanistically, circHIPK3 could directly bind to miR-124-3p and subsequently elevate the expression of the target gene MYH9 [ 143 ] Human MSCs In vitro NR lncRNA HOTAIRM1-1/miR-125b/ BMPR2; JNK/MAPK/ERK pathway HOTAIRM1-1 was downregulated in KOA cartilages and may inhibit MSCs viability, induce apoptosis, and suppress differentiation via regulating miR-125b/BMPR2 axis JNK/MAPK/ERK pathway may be a possible downstream mechanism to mediate the role of HOTAIRM1-1 in OA development [ 146 ] Human BM-MSCs-Exos In vitro NR lncRNA HOTTIP/miR-455-3p/CCL3 HOTTIP negatively regulated miR-455-3p and increased CCL3 levels in human chondrocytes [ 147 ] Human AT-MSCs In vitro NR circRNA_ATRNL1/miR‐145‐5p/SOX9 Circ_ATRNL1 regulated the promotion of SOX9 expression to promote chondrogenic differentiation of human AT-MSCs mediated by miR‐145‐5p [ 141 ] Human BM-MSCs-Exos Mice 10 µL, 500 µg/mL circRNA_0001236/miR-3677-3p/Sox9 Exosomal circRNA_0001236 enhanced the expression of Col2α1 and SOX9, but inhibited MMP13 in chondrogenesis via targeting miR-3677-3p and Sox9 [ 142 ] Human BM-MSCs In vitro NR lncRNA GRASLND Silencing of lncRNA GRASLND resulted in lower accumulation of cartilage-like extracellular matrix, while GRASLND overexpression significantly enhanced cartilage matrix production [ 144 ] …”
Section: Mechanisms In Cartilage Regeneration By Msc-based Cell Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of Runx2 partially reversed the effect of the SMSC-155-5p-Exos [ 136 ] MSCs-Exos In vitro, co-culture with mouse chondrocytes NR circRNA_HIPK3/miR-124-3p/MYH9 MSCs-Exos overexpressing circHIPK3 improved IL-1β-induced chondrocyte injury. Mechanistically, circHIPK3 could directly bind to miR-124-3p and subsequently elevate the expression of the target gene MYH9 [ 143 ] Human MSCs In vitro NR lncRNA HOTAIRM1-1/miR-125b/ BMPR2; JNK/MAPK/ERK pathway HOTAIRM1-1 was downregulated in KOA cartilages and may inhibit MSCs viability, induce apoptosis, and suppress differentiation via regulating miR-125b/BMPR2 axis JNK/MAPK/ERK pathway may be a possible downstream mechanism to mediate the role of HOTAIRM1-1 in OA development [ 146 ] Human BM-MSCs-Exos In vitro NR lncRNA HOTTIP/miR-455-3p/CCL3 HOTTIP negatively regulated miR-455-3p and increased CCL3 levels in human chondrocytes [ 147 ] Human AT-MSCs In vitro NR circRNA_ATRNL1/miR‐145‐5p/SOX9 Circ_ATRNL1 regulated the promotion of SOX9 expression to promote chondrogenic differentiation of human AT-MSCs mediated by miR‐145‐5p [ 141 ] Human BM-MSCs-Exos Mice 10 µL, 500 µg/mL circRNA_0001236/miR-3677-3p/Sox9 Exosomal circRNA_0001236 enhanced the expression of Col2α1 and SOX9, but inhibited MMP13 in chondrogenesis via targeting miR-3677-3p and Sox9 [ 142 ] Human BM-MSCs In vitro NR lncRNA GRASLND Silencing of lncRNA GRASLND resulted in lower accumulation of cartilage-like extracellular matrix, while GRASLND overexpression significantly enhanced cartilage matrix production [ 144 ] …”
Section: Mechanisms In Cartilage Regeneration By Msc-based Cell Therapymentioning
confidence: 99%
“…Moreover, circle-RNAs and long non-coding RNAs play vital roles in micro-RNAs interaction and show abnormal expression in osteoarthritis, which may be an important target for regulating osteoarthritis and for drug treatment. These RNAs regulate the progress of KOA by completing with micro-RNAs or other non-coding RNAs, that is called the ceRNA regulatory network, such as circRNA_ATRNL1 targeting miR‐145‐5p [ 141 ], circRNA_0001236 targeting miR-3677-3p [ 142 ], circRNA_HIPK3 targeting miR-124-3p [ 143 ], lncRNA GRASLND [ 144 ], lncRNA MEG3 targeting EZH2-mediated H3K27me3 [ 145 ], lncRNA HOTAIRM1-1 targeting miR-125b [ 146 ], lncRNA HOTTIP targeting miR-455-3p [ 147 ], lncRNA EPB41L4A‐AS1 and lncRNA SNHG7 targeting miR‐146a [ 148 ], and lncRNA LYRM4-AS1 targeting miR-6515-5p [ 149 ].…”
Section: Mechanisms In Cartilage Regeneration By Msc-based Cell Therapymentioning
confidence: 99%
“…Subsequently, subchondral plate densification will happen, which could finally lead to subchondral sclerosis, osteophytes formation, and cartilage loss in the late OA period [ 14 ]. Surprisingly, evidence proved that several circRNAs can regulate subchondral bone abnormal remodeling [ 8 , 41 , 42 ]. In this study, results showed that under shRNA-Circ_0000423 treatment, bone resorption decreased, then results in increased subchondral bone mass and joint bone integrity, which indicated that this treatment could reduce osteolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Further mechanism studies pointed out that BMSC-derived exosomal miR-136-5p facilitated chondrocyte migration and proliferation through targeting ELF3 and downregulating ELF3 expression in a traumatic OA mouse model ( Chen et al, 2020e ). In addition, BMSC-derived exosomal circular RNA (circRNA_0001236) could also facilitate cartilage repair through miR-3677-3p/Sox9 signaling axis ( Mao et al, 2021 ). Interestingly, Liu et al obtained an exosome via pretreating BMSC-derived exosome by a new small molecular compound Kartogenin.…”
Section: Exosomes and Bone Diseasesmentioning
confidence: 99%